Predicting Identity Formation in Adolescents based on Emotional Capital and Moral Disengagement Factors - Sajjad Khalafi (Iranian Journal of Educational Research)
Objective: The current investigation was undertaken with the objective of forecasting identity formation among adolescents, predicated upon the variables of emotional capital and moral disengagement. Methods: The methodology utilized in this inquiry is both descriptive and correlational in nature. The statistical population comprised all adolescents residing in Tehran during the year 2023, and a sample of 300 individuals was drawn utilizing a convenience sampling technique. Participants engaged with the research instruments provided. To facilitate data analysis, multiple linear regression analysis and Pearson's correlation coefficient test were employed through the application of SPSS version 26. Results: The results indicated that the constructs of emotional capital and moral disengagement possess the capacity to predict identity formation in adolescents. Specifically, the components of emotional capital, which include positive emotions, feelings of vitality, and happiness, were found to significantly and positively predict identity formation among adolescents. Furthermore, the factors associated with moral disengagement also demonstrated the capacity to inversely and significantly predict identity formation in this demographic. Conclusions: These findings, while affirming the critical influence of emotional capital and moral disengagement on the identity formation processes of adolescents, warrant consideration by stakeholders involved in the education and development of young individuals.